PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP FINANCIAL PERFORMANCE DENGAN FIRM SIZE SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SEKTOR BASIC MATERIALS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2024) - Tina Riyana; Nimas Aulia Pambajeng Miftahunnajah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of GCG on financial performance, with firm size as a moderating variable and leverage as a control variable, among manufacturing companies in the basic materials sector listed on the Indonesia Stock Exchange during the 2022–2024 period. This study employs a quantitative approach using panel data regression analysis. The research data consists of secondary data obtained from the IDX and the official websites of the relevant companies. The research sample consists of 138 companies. Sample selection was conducted using purposive sampling with E-views 12 software. The results indicate that managerial ownership, institutional ownership, and the audit committee do not have a significant effect on financial performance, whereas the independent board of commissioners has a significant negative effect. Firm size does not consistently moderate the relationship between Good Corporate Governance and financial performance; however, it can only strengthen the influence of the independent board of commissioners. Additionally, leverage has a significant negative effect on financial performance.